Pretransplant cancer in kidney recipients in relation to recurrent and de novo cancer incidence posttransplantation and implications for graft and patient survival - Unterrainer, Christian; Opelz, Gerhard; Döhler, Bernd; Süsal, Caner (Transplantation, 2019)
Background.Whether kidney transplant recipients who were treated for a malignant tumor before transplantation are at an increased risk of developing a tumor posttransplantation has not been adequately quantified and characterized.Methods.We studied more than 270 000 patients on whom pretransplant an
Gesehen am 09.03.2020